The effect of on-hill active recovery performed between runs on blood lactate concentration and fatigue in alpine ski racers - White, G. E.; Wells, G. D. (The Journal of Strength and Conditioning Research, 2015)
Alpine skiing is a high-intensity intermittent sport that results in lactate accumulation and muscle acidosis, which has been shown to contribute to peripheral neuromuscular fatigue. Active recovery influences the removal of lactate from the muscle and blood by maintaining blood flow to fatigued muscles and enhancing aerobic utilization of lactate by nonfatigued tissues. The purpose of this study was to investigate the effect of on-hill active recovery on blood lactate concentration in alpine skiers. Fourteen highly trained alpine skiers (7 women, 7 men) completed 8 training runs in a 45-gate slalom or a 25-gate giant slalom corridor at 2,600 m above sea level. Skiers were randomized to active (ACT) or static recovery (CON) performed at the top of each run. Blood lactate concentration and perceived fatigue were recorded at the top and bottom of each run. Performance was measured by time to complete each training run and rate of incomplete runs. A significant time (p < 0.01) and interaction (p = 0.001) effect was observed for blood lactate concentration measured at the top, with ACT being associated with significantly lower values. A significant time effect (p < 0.001) was observed for blood lactate concentration measured at the bottom. Training run completion time was longer (p = 0.05), and higher rate of incomplete runs were observed in the CON group, despite no between-group differences in rating of perceived fatigue. On-hill active recovery performed between runs promotes blood lactate clearance in alpine skiers and is associated with delayed fatigue as indicated by faster training runs and fewer incomplete runs.